The effectiveness of technological resources applied as didactic tools in the english language learning process to students of 9th level at the Beatriz Miranda de Cabal High School located in Dolega, Chiriquí - Acosta M., Beatriz (David, Panamá : UDELAS, 2011)
Far many years, people around the world have tried to use technology as a teaching resources for the teaching of the english language. Furthemore, this issue has become very important in the educational field as it came to make changes to traditional ways of teaching and learning with the purpose to increase and improve the effectiveness of teachers' tasks at the same time students' uderstanding.
GENERAL INDEX Though Acknowldgement Dedication General index Chart index Graphic index Appendix index Introduction CHAPTER I: FORMULATION OF THE PROBLEM CHAPTER II: FORMULATION OF THE PROBLEM 2.1. New technological resources applied as didactic tool in the english language learning process 2.1.1. Definition 2.1.2. New useful technologies using in education 2.1.3. The role of technologyin education 2.1.4. The role of play it in the learning process 2.1.5. Characteristics 2.1.6. New possibilities in education 2.1.7. Motivation and learning 2.2. Teachers and students interaction with technological resources applied as didactic tools in the english language learning process 2.2.1. The new teacher's role 2.2.2. The new student's role 2.3. Level of acceptance of technological resources applied as didactic tool in the english language learning process by teachers and students, at the same time 2.3.1. Positive acceptance 2.4. Negative factors of technology as a didactic resources in the second language acquisition 2.4.1. Negatives aspects 2.4.2. Disadvantages CHAPTER 3: RESEARCH METHODOLOGY CHAPTER 4: ANALYSIS AND INTERPRETATION OF THE RESULT CAPTER 5: PRESENTATION OF THE PROPOSAL Appedix Conclusion Recommendation Bibliography
Incluye General index
Documento presentado para optar por el título de Licenciatura en Docencia en Inglés
Incluye Bibliografía
No se presta a domicilio
No se saca fotocopia
Keywords: ENGLISH -- TESIS DE LICENCIATURA -- LEARNING; ENGLISH -- TESIS DE LICENCIATURA -- TECHNOLOGICAL RESOURCES; FACULTAD DE EDUCACIÓN SOCIAL Y ESPECIAL; LICENCIATURA EN DOCENCIA EN INGLÉS; BEATRIZ MIRANDA DE CABAL HIGH SCHOOL - CHIRIQUÍ